Mechanistic analysis of the hardening process of the thorns on stems of Bougainvillea glabra “Elizabeth Angus” - Sun, Lina; Wang, Huaxin; Li, Jinhua; Gong, Jianying; Yang, Shuting; Yang, Kaitai; Chen, Er; Li, Bing; Lu, Zhixiang; Chen, Qi; Lin, Mao (Frontiers in Genetics, 2024)
Bougainvillea glabra 'Elizabeth Angus' is a thorny woody vine or shrub. However, the hard thorns are considered a deficiency in its ornamental value. To find the genes and pathways related to the hardening process of the thorns on the stems of B. glabra, the eukaryotic unreferenced transcriptome sequencing analysis was conducted to explore the 3 stages of the thornhardening process. Total RNA was extracted from thorns and stems, and transcriptome libraries were constructed and sequenced using unreferenced Illumina sequencing. Gene function annotation was performed using various databases, resulting in 8937 co-annotated genes. The density distribution of Fragments Per Kilobase of transcript per Million mapped reads (FPKM) depicted the overall gene expression patterns. The study found that stage 2 as the period of highest gene expression activity during the thorns hardening process in B. glabra. Differential expression analysis revealed that during thorn-hardening, 1045 genes up-regulated and 391 genes downregulated significantly in thorns at stage 2 compared to stage 1 (early stage of thorns formation).Meanwhile, 938 genes up-regulated and 784 genes down-regulated significantly in stems. At stage 3, as thorns became harder, 63 genes exhibited notable expression increase and 98 genes' expression decreased obviously within thorns, and 46 genes up-regulated and 29 genes downregulated in stems, compared to stage 2. Phenylpropanoid biosynthesis was the key step in the hardening process of the thorns of B. glabra. The formation and hardening of thorns on the stem of B. glabra was a process in which lignin gradually accumulated in the thorns, and several genes were involved in this process. They include PAL (EC:4.3.1.24) , CYP73A (EC:1.14.14.91), 4CL (EC:6.2.1.12), CCR (EC:1.2.1.44), CAD (EC:1.1.1.195) and POX (EC:1.11.1.7). This transcriptome analysis offers insights into the molecular mechanisms underlying thorns development in this plant species.